Arthroplasty Utilization in the United States is Predicted by Age-Specific Population Groups. (23rd October 2012) - Bashinskaya, Bronislava; Zimmerman, Ryan M.; Walcott, Brian P.; Antoci, Valentin
Abstract : Osteoarthritis is a common indication for hip and knee arthroplasty. An accurate assessment of current trends in healthcare utilization as they relate to arthroplasty may predict the needs of a growing elderly population in the United States. First, incidence data was queried from the United States Nationwide Inpatient Sample from 1993 to 2009. Patients undergoing total knee and hip arthroplasty were identified. Then, the United States Census Bureau was queried for population data from the same study period as well as to provide future projections. Arthroplasty followed linear regression models with the population group >64 years in both hip and knee groups. Projections for procedure incidence in the year 2050 based on these models were calculated to be 1, 859, 553 cases (hip) and 4, 174, 554 cases (knee). The need for hip and knee arthroplasty is expected to grow significantly in the upcoming years, given population growth predictions.